High-throughput mutational analysis of a methyltransferase ribozyme - Yamagami, Ryota; Kubota, Hina; Kohno, Emi; Hori, Hiroyuki (Frontiers in RNA Research, 2024)
Methyltransferase ribozyme 1 (MTR1) is a catalytic RNA that has been isolated from a random RNA pool by in vitro selection. The ribozyme catalyzes site-specific formation of 1-methyl adenosine (m 1 A) using 6-methyl guanine (m 6 G) as a methyl group donor. The ribozyme has been extensively characterized by biochemical and structural analyses. Here, we describe high-throughput screening of single point mutants in the catalytic domain of MTR1 and determine their effect on ribozyme activity. Our mutational profiling method successfully assessed the activity of the 141 MTR1 variants tested in each experiment and revealed that the ribozyme is very sensitive to nucleotide substitutions in the catalytic core domain. Our technique can be applied to methyltransferase ribozymes that catalyze formation of different modifications such as 7-methylguanosine (m 7 G) or 3-methylcytidine (m 3 C).